2019
DOI: 10.2298/pif1901031t
|View full text |Cite
|
Sign up to set email alerts
|

Fungal biodiversity on maize kernels in an insecticide evaluation trial

Abstract: The European corn borer (ECB) Ostrinia nubilalis and Fusarium ear rot Fusarium spp. pose a continuous threat to maize production worldwide. There are several reports indicating that ECB damage to maize ears promotes Fusarium ear rot infection. The aim of this study was to monitor the influence of different insecticide treatments (a.i. chlorantraniliprole, indoxacarb, and chlorantraniliprole+lambda-cyhalothrin) on the ECB and fungal diversity on maize kernels in the field in a four-year trial (2013-2016). A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The identified species of Fusarium were F. proliferatum, F. subglutinans, F. graminearum, and F. verticillioides. Furthermore, according to the findings of Tančić Živanov et al [34] in a recent study, 11 species of Fusarium were found in the grains of two different commercial maize varieties that were cultivated in Serbia. Among these species, F. graminearum, F. verticilioides, and F. graminearum were the most commonly identified.…”
Section: Comparative Studymentioning
confidence: 88%
“…The identified species of Fusarium were F. proliferatum, F. subglutinans, F. graminearum, and F. verticillioides. Furthermore, according to the findings of Tančić Živanov et al [34] in a recent study, 11 species of Fusarium were found in the grains of two different commercial maize varieties that were cultivated in Serbia. Among these species, F. graminearum, F. verticilioides, and F. graminearum were the most commonly identified.…”
Section: Comparative Studymentioning
confidence: 88%